Non-invasive surface electroencephalography for broilers - Yukari Togami; Jolien Hacker; Elke Rauch; Michael Erhard; Helen Louton (MethodsX)
Our research aimed to develop a non-invasive EEG method for broiler chickens that can be utilized in basic research and practical applications. We evaluated the success of 1) the application and attachment of the EEG electrodes to the head of broiler and 2) measurements of EEG with non-invasive surface electrode (NISE). With this publication we would like to make the method NISE accessible to other researcher. We used a mobile EEG system with a combination of three surface electrodes, with a diameter of 8 mm. The mobile EEG device is carried by the broiler chickens in a backpack during the recording. Of the 52 broiler chickens examined using EEG, baseline data in a calm state was successfully recorded for 30 ss in 45 animals without significant artifacts. Measurement of EEG with a distance of 1 meter between the laptop and the EEG device in the backpack on the animal was successful, suggesting that this method could have broader applicability in practical environments in the future. • The use of EEG measurements in veterinary research has grown. • A non-invasive EEG technique for broiler chickens, suitable for both fundamental research and practical applications (NISE). • A non-invasive method is more conducive to animal welfare.